A monster calls : a novel - Ness, Patrick, 1971-; Kay, Jim (Somerville, Mass. : Candlewick Press, 2011)
Thirteen-year-old Conor awakens one night to find a monster outside his bedroom window, but not the one from the recurring nightmare that began when his mother became ill--an ancient, wild creature that wants him to face truth and loss.
Booklist starred
Pub Weekly
School Library Journal starred
Booklist starred, July 2011
Bulletin (Center for Children's books), November 2011
Horn Book, September 2011
Keywords: Breast cancer -- Juvenile fiction; Loss (Psychology) -- Juvenile fiction; Monsters -- Juvenile fiction; Mothers and sons -- Juvenile fiction; Schools -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Single-parent families -- Juvenile fiction; Breast cancer -- Fiction; Loss (Psychology) -- Fiction; Monsters -- Fiction; Mothers and sons -- Fiction; Schools -- Fiction; Self-actualization (Psychology) -- Fiction; Single-parent families -- Fiction; Breast cancer -- Fiction; Loss (Psychology) -- Fiction; Monsters -- Fiction; Mother-son relationship -- Fiction; School stories; Self-realization -- Fiction; Single-parent families -- Fiction; England -- Juvenile fiction; England -- Fiction; England -- Fiction